2006
DOI: 10.1038/emm.2006.18
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A-dependent phosphorylation of B/K protein

Abstract: We have previously isolated a novel protein "B/K" that contains two C2-like domains. Here, we report the isolatioin and mRNA distribution of a human B/K isoform, and protein kinase A (PKA)-dependent phosphorylation of the B/K protein. The 1.5 kb human B/K cDNA clone exhibits 89% and 97% identities with rat B/K in the sequences of nucleotide and amino acid, respectively. Human B/K isoform encodes a 474 amino acid protein and shows structural features similar to the rat counterpart including two C2 domains, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The secondary 16p12.3 peak lies over another candidate gene, SYT17 (synaptotagmin17), which is abundantly expressed in frontal and temporal lobes (Chin et al . ). The 16p11‐p13 region has been previously linked to dyslexia in two microsatellite genome‐wide scans (16p12.2, D16S3046, lod 2.2–2.4, Loo et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The secondary 16p12.3 peak lies over another candidate gene, SYT17 (synaptotagmin17), which is abundantly expressed in frontal and temporal lobes (Chin et al . ). The 16p11‐p13 region has been previously linked to dyslexia in two microsatellite genome‐wide scans (16p12.2, D16S3046, lod 2.2–2.4, Loo et al .…”
Section: Discussionmentioning
confidence: 97%
“…Protein kinase C is known to regulate cognitive functioning in the prefrontal cortex (Chen et al 2009) (note also PRKCE at 2p21 linkage region; Table 1). The secondary 16p12.3 peak lies over another candidate gene, SYT17 (synaptotagmin17), which is abundantly expressed in frontal and temporal lobes (Chin et al 2006). The 16p11-p13 region has been previously linked to dyslexia in two microsatellite genome-wide scans (16p12.2, D16S3046, lod 2.2-2.4, Loo et al 2004;16p11.2, D16S753, lod 2.9, Raskind et al 2005), to ADHD in two scans (16p13, lod 3.7, Ogdie et al 2004;16p13, lod 2.4, Gayan et al 2005) and to autism (16p13, D16S3102, lod 2.9, IMGSAC 2001).…”
Section: Putative Linkage Regions (Lod >23)mentioning
confidence: 99%
“…Calcium binding to synaptotagmin I participates in triggering neurotransmitter release at the synapse [Fernandez-Chacon et al, 2001]. SYT17 is a protein''B/K'' isoform expressed strongly in the frontal and temporal lobes, the hippocampus, the hypothalamus, the amygdala, the substantia nigra, and the pituitary [Chin et al, 2006]. Interestingly, another member of this family of genes, the synaptotagmin 4 (SYT4), maps to 18q12.2, a region that we [Maziade et al, 2005] and others have shown to be linked to BP and SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptotagmin XVII (B/K protein) has been found in the ER in rat hippocampus (Jang et al. 2004) and revealed an abundant presence in the brain, kidney and prostate (Chin et al. 2006).…”
Section: Novel Candidatesmentioning
confidence: 99%